Management of advanced Parkinson’s disease in Israel: Clinicians viewpoint and action items - Gurevich, Tanya; Arkadir, David; Badarny, Samih; Benizri, Sandra; Cohen, Oren; Djaldetti, Ruth; Hassin-Baer, Sharon; Kestenbaum, Meir; Nitsan, Zeev; Zlotnik, Yair; Yahalom, Gilad (Frontiers in Aging Neuroscience, 2022)
Parkinson’s disease (PD) is taking a staggering toll on healthcare systems worldwide, with the bulk of the expenditures invested in the late stages of the disease. Considering the rising life expectancy and the increasing prevalence of PD across the globe, a clear understanding of the early signs and treatment options available for advanced PD (APD), will facilitate tailoring management programs and support services. This task is complicated by the lack of both global consensus in defining APD and standardized care guidelines. This perspective prepared by a panel of movement disorder specialists, proposes to extend and optimize currently accepted PD coding to better reflect the diverse disease manifestations, with emphasis on non-motor features. The panel seeks to promote timely diagnosis by adjustment of evaluation tools for use by community neurologists and suggests modification of eligibility criteria for advanced therapy. Moreover, it advocates multidisciplinary assessments of APD patients to drive personalized, patient-centered and holistic management. Overall, earlier and more targeted intervention is expected to markedly improve patient quality of life.